MENINGKATKAN KEPUTUSAN PEMBELIAN RETAIL MELALUI KEPUASAN KONSUMEN DI BANDARA SOEKARNO-HATTA; KONTRIBUSI PERSEPSI HARGA DAN STORE LAYOUT - Setiawan, Edhie Budi; Fahriza, Basri; Satyagraha, Anggit; Abidin, Zaenal; Arubusman, Dian Artanti (Gorontalo Management Research, 2023)
The airport business is a growing and promising business. The increase in the number of trips will automatically have an impact on airport revenues. Currently, airport revenue is still dominated by revenue from the aeronautical sector, while the potential for non-aeronautical revenue is also quite promising. The retail business at the airport is one of non-aeronautical businesses that has big opportunities with potential to be a significant alternative income for the airport. This study was addressed to examine the effect of store layout and price perception on retail purchasing decisions at the airport mediated by consumer satisfaction. It uses a quantitative method, with 100 respondents, where they fill out online questionnaires. The analytical technique used is SEM-PLS. The results showed that the store layout and price perception have a positive and significant influence on purchasing decisions and on consumer satisfaction at the same time, whilst consumer satisfaction also has a positive and significant influence on purchasing decisions. Store layout and price perception have an indirect influence on purchasing decisions through consumer satisfaction. Based on these results, airport managers are expected to pay more attention to marketing strategies that focus on creating attractive store layouts and competitive prices, so that consumers feel satisfied and decide to make a purchase.Keyword: consumer satisfaction, buying decision, price perception, airport retail, store layout